Evaluation of antinociceptive activity of 2-benzoyl-6-(3-bromo-4-hydroxybenzylidene)cyclohexen-1-ol and its possible mechanisms of action in mice - Ong, Hui Ming (2021)
Pain is one of the frequent reasons that one seeks for medical attention. Opiates and of non-steroidal anti-inflammatory drugs (NSAIDs) are the common treatments for various kinds of pain. However, the use of opiates often leads to undesirable effects such as constipation, nausea and even addiction. Besides, prolonged usage of NSAIDs tends to develop gastrointestinal and cardiovascular dysfunctions in one’s body. Therefore, there’s an urgent need to accelerate the drug discovery for new potent antinociceptive compound with equivalent painkilling effect as the contemporary analgesics, but with minimal or no adverse effects. The general objective of the present study was to determine the antinociceptive activity of 2-benzoyl-6-(3-bromo-4-hydroxybenzylidene) cyclohexen-1-ol (BBHC) at peripheral and central levels of nociception. Our specific objectives were to study the antinociceptive property of BBHC against peripheral inflammatory mediators, and also to investigate the participation of BBHC in excitatory neurotransmission and central descending inhibitory pathways (opioid and non-opioid pathways). The preliminary antinociceptive activity of BBHC was screened with 3 antinociceptive tests, acetic acid-induced abdominal constriction test, formalin-induced paw licking test and hot plate test. Upon the confirmation of BBHC’s inhibitory effect against the chemically- and thermally-induced nociception, BBHC was subjected to investigate for its possible mechanisms of action towards peripherally-mediated inflammatory mediators, excitatory neurotransmitters and a range of pain-modulating receptors from descending inhibitory pathways. The findings from our present study showed that BBHC significantly inhibited chemically- and thermallyinduced pain from the 3 antinociceptive screening tests. BBHC had also reduced pain caused by various inflammatory mediators and excitatory neurotransmitters. The antinociception of BBHC was indicated to be associated with descending inhibitory modulations, such as α2-adrenoreceptor, 5-HT1A receptor, GABAA receptor, A1 adenosine receptor, D2-like dopaminergic receptor and L-arginine-NO-cGMP-K+ channels pathway. Despite the significant antinociceptive property of BBHC, it was confirmed that BBHC’s analgesic activity is not related to muscle relaxation and sedation. BBHC’s LD50 was proven to be greater than 2000 mg/kg which then classified BBHC as Category 5 according to the globally Harmonised System for classification of chemicals. As conclusion, the present study has shown that BBHC-induced analgesia is mediated by peripheral and central pain modulations of peripheral inflammatory mediators, neurotransmitters and descending inhibitory pathways.